P79 Quantifying Physical Activity For 30 Days Via Pedometry in COPD Patients. (19th November 2012) - Alahmari, AD; Donaldson, GC; Patel, ARC; Kowlessar, BS; Mackay, AJ; Singh, R
Abstract : Introduction: Physical activity and exercise capacity are among the important patient-relevant parameters in COPD. COPD patients are less active and less likely to go outside when compared with the general population and this worsens during exacerbation (1). The aim of this study was to determine whether step-counts measured by a pedometer (Yamax Digi-walker SW-200) would be a useful method of quantifying physical activity in stable COPD patients on the community. Methods: Stable COPD outpatients wore a pedometer for 30 days, had a six minute walk distance (6MWD) assessed according to ATS protocols and completed the SGRQ (St. George's Respiratory Questionnaire) and MRC dyspnoea score. The pedometer was worn on the left-hand side during waking hours. Patients recorded daily step counts and time spent outdoors on written daily diary cards. Results: Fifty-five COPD patients had a mean (±SD) age 70.3 (8.7) years and FEV1 51.0% predicted (±14.1); male gender 67%. The mean (±SD) 6MWD was 416 (±88) metres, with an average of 4327 (±2944) steps/day and spent 3.1 (±1.4) hours outdoors. Figure 1 shows that patients with greater 6MWD took more steps per day during normal activity [r=0.47; p=0.001], Fig. 1A, and stayed outdoors for longer [r=0.41; p=0.003], Fig. 1B. Patients with lower step counts tended to have a poorer health status in terms of SGRQ score[r= –0.31; p=0.025], Fig. 1C, and a higher level of dyspnoea on the MRC score [Rho= –0.39; p=0.005], Fig. 1D . Conclusions: Daily step counts measured by a pedometer averaged over 30 days correlated well with objective tests of physical capacity, time outdoors, health status and dyspnoea. Thus pedometry is a useful method of quantifying daily physical activity in COPD patients. References: Donaldson GC et al ., Exacerbations and Time Spent Outdoors in Chronic Obstructive Pulmonary Disease, Am J Resp Crit Care Med (2005) 171: 446–452.